"Quaint creatures": public discourse and the role of B-girls in the heritage of Bourbon Street. Issue 4 (1st October 2016) - Demovic, Angela R.
ABSTRACT: B-drinking is soliciting a patron to purchase the B-girl a drink for which she receives a commission; this strategy has long been an integral and accepted part of French Quarter culture. Invisible in the academic literature, B-girls are an important part of heritage tourism in New Orleans. In a tourism city famous for alcohol, sex, and vice, B-drinkers are an important service labor force that drives the strip clubs at the center of the touristscape. Since the middle of the twenty-first century, B-drinking has played a crucial role in the sexual economy of tourism on Bourbon Street. B-girldom provides a case study in how the intersection of tourism and sex work is deeply embedded in regional history. The discursive B-girl as constructed in newspapers, media, and the legislature reflects local shifts in attitudes towards B-drinking from 1941 to 2012. B-girls, constructed as flirtatious tricksters or dangerous murderers, are icons of the French Quarter and an embedded fixture in this heritage tourism site – illegal but authentic inhabitants of Bourbon Street. Representations of B-girldom by powerful voices have long acknowledged and defined how sex workers engage within the French Quarter in ways understood and accepted by the people of New Orleans.